2023
DOI: 10.1021/acsapm.3c00542
|View full text |Cite
|
Sign up to set email alerts
|

Washable Antibacterial Modified Bio-based PA56 with High Toughness

Abstract: An effective method was developed for the preparation of a washable antibacterial modified bio-based polyamide 56 (PA56) with high toughness by a simple reactive extrusion technique. In this work, polypentamethylene guanidine hydrochloride (PPMG), as a bio-based antibacterial reagent, was successfully grafted onto a bio-based PA56 polymer. The micromorphology of the samples was studied by scanning electron microscopy, which proved that the addition of ethylene-methyl acrylate-glycidyl methacrylate terpolymer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Importantly, the value of HC 50 indicated that PPGS had a certain physiological toxicity. Therefore, in practical application, PPGS is recommended to be combined with materials by chemical bonding to prepare nondissolved antibacterial materials …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the value of HC 50 indicated that PPGS had a certain physiological toxicity. Therefore, in practical application, PPGS is recommended to be combined with materials by chemical bonding to prepare nondissolved antibacterial materials …”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, they are safe for humans and animals. In particular, their excellent heat resistance renders them widely useful in the field of plastic antibacterial modification. Recently, polypentamethylene guanidine hydrochloride (PPMG), which is synthesized from biobased pentamethylene diamine, has attracted significant attention as a green antibacterial agent. , However, similar to the use of ordinary guanidine salts, the long-term use of this antibacterial agent corrodes the processing equipment, specifically at high temperatures . During the normal corrosion process, a passivation film is formed on the metal surface, which changes the state of the metal from active to passive, thus improving its corrosion resistance. , When active halogen ions come into contact with metal surfaces due to their small size, they diffuse easily into the metal passivation films and increase the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%